2017
DOI: 10.1103/physrevx.7.041015
|View full text |Cite
|
Sign up to set email alerts
|

Driven Quantum Dynamics: Will It Blend?

Abstract: Randomness is an essential tool in many disciplines of modern sciences, such as cryptography, black hole physics, random matrix theory, and Monte Carlo sampling. In quantum systems, random operations can be obtained via random circuits thanks to so-called q-designs and play a central role in condensed-matter physics and in the fast scrambling conjecture for black holes. Here, we consider a more physically motivated way of generating random evolutions by exploiting the many-body dynamics of a quantum system dri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(65 citation statements)
references
References 81 publications
1
64
0
Order By: Relevance
“…The distribution for staggered hopping, Fig. 11-(b) clearly presents level repulsion and suppression at small angles, with − cos θ = 0.2356 (24) and r = 0.7382 (7). Both effects are compatible with the Ginibre universality class (recall that, for 10 4 × 10 4 matrices from the GinUE, we found − cos θ = 0.24051(61) and r = 0.73810 (18)).…”
Section: Numerical Resultsmentioning
confidence: 55%
“…The distribution for staggered hopping, Fig. 11-(b) clearly presents level repulsion and suppression at small angles, with − cos θ = 0.2356 (24) and r = 0.7382 (7). Both effects are compatible with the Ginibre universality class (recall that, for 10 4 × 10 4 matrices from the GinUE, we found − cos θ = 0.24051(61) and r = 0.73810 (18)).…”
Section: Numerical Resultsmentioning
confidence: 55%
“…Indeed, while we have used quantum optimal control to reach a desired target Haar-random unitary, such fine-tuned control may not be required. Since a random control waveform should yield a pseudorandom transition matrix after a suitably long mixing time (see [85]), we expect this time might be much shorter than that required to reach a particular target chosen from Haar random unitary matrices. This could lead to a more efficient and scalable approach to Boson Sampling.…”
Section: Discussionmentioning
confidence: 99%
“…We remark here that the N-level system has recently been analyzed in great detail in [47] for the case when one control is present and the control field is chosen randomly. Based on unitary q-designs it was shown that the time to implement a generic goal gate operation scales as ( ) N 3 .…”
Section: N-level Systemmentioning
confidence: 99%